A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMP MUHAMMADIYAH 1 PEKANBARU IN WRITING DESCRIPTIVE TEXTS - Iradatul Hasanah; Effendy Gultom; M. Nababan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is entitled “A Study on the Ability of the Second Year Students of SMP Muhammadiyah 1 Pekanbaru in Writing Descriptive Texts. This study concerns with five aspect of writing. They are: Grammar, Vocabulary, Mechanic, Organization, and Fluency. The aim of this study is to find out the ability of the second year students of SMP Muhammadiyah 1 Pekanbaru in writing Descriptive text. The data collecting technique is using a writing test. The students’ writing results are checked and scored by three raters. They are Elmalia Santos S.S, Erva Yanti S.Pd, and Rita Dwi Indah Wulandari S.Pd. The writer chose these three raters because they teach English in junior high school and they have experienced as an English teacher. Thus ,their assessments are believed and to be a reference in collecting the data.The research findings are as follows: first, the ability of the second year students in writing descriptive texts is in good level with the average score of 62.75. Second, the students’ average score in terms of Grammar is 61.80, in terms of Vocabulary is 68.80, in terms of Mechanic is 70.02, in terms of Organization is 61.80, and in terms of Fluency is 52.40. It is the most difficult problem faced by the students in writing descriptive texts. The findings show that the second year students of SMP Muhammadiyah 1 Pekanbaru have relatively good level in writing descriptive texts. But with the average score of 62.75, they need to practice more in writing a text.Key Words: Study, Ability, Writing, Descriptive Texts.